Improving Reading Skills for at-Risk Pupils in Early Grades in Tanzanian Primary Education through Dynamic Teaching and Assessment Strategy - Salvius Kumburu; Tandika Pambas (An Overview of Literature, Language and Education Research Vol. 8, 2024)
The study assessed the efficacy of the Dynamic Teaching and Assessment (DTA) strategy in improving reading skills for at-risk pupils’ early graders in Tanzania in selected primary schools in the Dodoma region. The randomized quantitative study was employed characterized by the pre-test and post-test research design. The test Battery constructed through Kiswahili language content was administered to 407 (234 grade one and 173 grade two girls) aged between eight (8) and nine (9) years old respectively. The pupils from both grades were divided into one experimental group and one control group. In grade one, 111 (55 boys; 56 girls) formed an experimental group; whereas, 123 (53 boys and 70 girls) formed the control group. In grade two, 102 (50 boys and 52 girls) formed the experimental group while 71 (36 boys and 35 girls) formed the control group. Both, the experimental and control groups for all the grades set for a pre-test in which their scores were recorded for the purpose of comparison in the post-testing. Both, the experimental and the control groups underwent training on Kiswahili language content for six weeks, whereby, the experimental groups received the training through DTA. A post-test was administered at the end of the sixth week for both groups. Repeated ANOVA was used to determine the mean differences of the test scores of both the pretest and posttest of the grade one and two pupils. The analysis indicated that the experimental group in each grade improved their reading ability significantly compared to the control groups. The study concludes that the DTA as a teaching and assessment strategy was significantly effective in improving the at-risk pupils’ reading skills in the target language. The findings suggest that DTA be incorporated into reading instruction to benefit pupils who struggle with reading.